Kinetic study on the activation of PhICl2 with Lewis bases for aromatic chlorination. Issue 32 (1st August 2022) - Davis, Benjamin A.; Tania; Dutton, Jason L.
Abstract : A kinetic study on the chlorination of arenes with nucleophilically activated PhICl2 experimentally demonstrates the nucleophile induces elimination of chlorine gas. Abstract : A study on the kinetics of the activation of PhICl2 using catalytic chloride or pyridine in electrophilic chlorination of arenes has been carried out. The results indicate that both catalysts induce the release of Cl2 from PhICl2 and that the Cl2 is the active reagent for chlorination in these reactions.